Service Quality at Technical and Vocational Education and Training Colleges: Perception According to Demographic Factors - Mason, Roger Bruce; Mbambo, Sbongiseni Nelson; Pillay, & Magalingam Atheeshey (Journal of Technical Education and Training, 2018)
TVET colleges are regarded as second-class educational institutions in South Africa. As a result, their enrolment targets are not being met, which is a problem for the development and growth of this educational sector. The objective of this paper is to identify whether students’ satisfaction with the service quality provided by TVET colleges differ according to selected demographic factors, and thus help to understand specific reasons for not meeting their enrolment targets. A survey of 301 respondents from six colleges, using a SERVQUAL questionnaire, comprised the methodology. The results showed little difference in satisfaction with service quality according to the demographic factors tested – all respondents were more or less equally dissatisfied with the service quality of their TVET colleges. Therefore, looking for reasons for the poor enrolment levels amongst the different demographic characteristics of the students is pointless. The poor service quality perceived is probably due to inadequate systems, or inadequate management or staff training, rather than failure to meet specific needs of students from different demographic types. Recommendations are provided for overcoming the poor service, and for further research.